2013
DOI: 10.2176/nmc.oa2012-0307
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Characteristics of Idiopathic Normal Pressure Hydrocephalus: A Diffusion Tensor Tract-Based Spatial Statistic Study

Abstract: Using magnetic resonance-diffusion tensor imaging (DTI), we examined white matter changes within the brains of patients diagnosed with idiopathic normal pressure hydrocephalus (INPH). We analyzed data for 24 INPH patients who were presented with typical clinical symptoms (gait disturbance, dementia, and/ or urinary incontinence) and Evans index > 0.3, and compared these with the control data from 21 elderly persons (≥ 60 years). DTI brain images were obtained with a 3T scanner. Fractional anisotropy (FA) brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 41 publications
0
35
1
1
Order By: Relevance
“…26 in the previous report. 9) auditory radiations bilaterally. The fiber tracking analysis employed the MGB as seed voxels and indicated disruption of the acoustic fibers.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…26 in the previous report. 9) auditory radiations bilaterally. The fiber tracking analysis employed the MGB as seed voxels and indicated disruption of the acoustic fibers.…”
Section: Resultsmentioning
confidence: 97%
“…The details of MRI acquisition sequences have been published elsewhere. 9) For image processing, we used the FMRIB Software Library (FSL), 10,11) which is a command-line programmable brain image analysis package. To better characterize the lesion sites in this patient, we enrolled three control subjects whose ages were similar to the patient's.…”
Section: Case Reportmentioning
confidence: 99%
“…9,16,41,45,48,55,57,59,75,84,94,125 Understanding the periventricular white matter tracts is helpful not only in defining more precise surgical strategies, but also in clarifying the symptoms of and appropriate treatment for patients with hydrocephalus and periventricular lesions. 11,18,36,38,40,47,50,52,58,65,66,76,80,101 This study examines the tracts at risk in the 3 surgical routes-anterior, posterior, and lateral-to the lateral ventricle. The anterior approaches include the anterior interhemispheric transcallosal, anterior frontal transcortical, and anterior frontal interhemispheric transrostral; the posterior approaches include the posterior transcortical (superior parietal lobule), posterior interhemispheric transcallosal, posterior interhemispheric precuneal, supracere- …”
Section: Discussionmentioning
confidence: 99%
“…MR tractography has been recommended as a means of differentiating among NPH, AD, and PD. 36,38,40,47,50,52,65,66,76 Hydrocephalus studies have suggested that the compression indicated by high fractional anisotropy (FA) levels will eventually cause the neuronal degeneration, brain edema, or deterioration of the white matter indicated by low FA levels.…”
Section: Periventricular Tracts In Hydrocephalusmentioning
confidence: 99%
“…8,49,50 Several researchers have underlined the significance of DTI-based methods for diagnosing iNPH. 14,15,29,30,42,45 A plethora of different DTI protocols for examining various areas of the brain have been described in the literature, including manual ROI placement, TBSS, tract-specific, voxel-based, and delta-ADC analyses. The most frequently studied regions in patients with iNPH are the periventricular WM areas such as the IC, CST, and CC, as well as the frontal, temporal, and occipital lobes and the cerebral peduncles.…”
Section: Discussionmentioning
confidence: 99%